Progress in the physics of clusters - Chuev, G. N. (World Scientific, 1999)
The findings reported in this book on the methods of cluster measurements will lead to new avenues using nondestructive mass spectrometry and dipole mass isomers.Much attention is given to the physics and chemistry of fullerenes and nanotubes, including the problems surrounding the formation and growth of nanotubes, electron characteristics of fullerenes, the influence of solvents, simulation of the properties of carbon clusters, etc. Some unique experimental data on the conversion of aerosols into aerogels with the formation of fractal structures is provided. In addition, the book covers one of the most interesting subjects of modern physics - fractal clusters.Quantitative information on the thermodynamic properties of transition metal clusters, their binding energies to various ligands, and their reactions is obtained using a metal cluster guided ion beam mass spectrometer. Measurement of the thermodynamic stability of transition metal clusters is reported.